Contextual Bureaucratic Reform in the Recruitment System of the State Civil Apparatus of Indonesia - Vincent Simandjorang, Bonataon Maruli Timothy; Kurniawan, Andhi (KnE Social Sciences, 2022)
Bureaucratic reform is important for achieving the vision of a sovereign, advanced, equitable and prosperous Indonesia in preparation for the centennial celebration of Indonesia’s independence in 2045. Improvement of public services within the framework of bureaucratic reform can be initiated with a good procurement or recruitment system for the state civil apparatus (ASN). Computer assisted tests were implementated in 2013, and the recruitment of prospective civil servants is increasingly fair, transparent and effective in attracting good quality candidates in line with the needs of the organization. However, ASN recruitment still encounters a number of problems ranging from formation, infrastructure and types of tests to the lack of interest from the diaspora community, persons with disabilities and other talented professionals to join and serve their country as civil servants. These weaknesses and constraints need to be solved immediately to capture the nation’s best talents for the achievement of the Indonesia Vision 2045 agenda. This study aimed to carry out a comprehensive evaluation of ASN recruitment policies and develop policy recommendations for the recruitment of civil servants. A qualitative approach was used, and data were collected through a literature search and in-depth interviews. The findings can be used as a reference to support world-class bureaucracy in Indonesia. Keywords: recruitment system, civil servants, bureaucratic reform